IDENTIFIKASI REHABILITASI DAN PEMELIHARAAN INFRASTRUKTUR JALAN: SYSTEMATIC LITERATURE REVIEW - Lalu Sulthonul Azmi; Faeruzza Athiya (Journal of Innovation Research and Knowledge, 2026)
Road infrastructure plays a strategic role in supporting mobility, safety, and economic growth. However, pavement deterioration caused by traffic loads, environmental factors, and limited maintenance remains a major issue in many regions. This study aims to identify road rehabilitation and maintenance approaches using a Systematic Literature Review (SLR) method. The reviewed literature covers road damage identification, pavement condition assessment, condition-based maintenance planning, digital technology utilization, and environmental impacts of road rehabilitation. The results indicate that pavement condition assessment methods such as the Surface Distress Index (SDI), Pavement Condition Index (PCI), and Mechanistic-Empirical Pavement Design Guide (MEPDG) are effective in determining appropriate maintenance and rehabilitation strategies. Furthermore, the integration of Geographic Information Systems (GIS), Digital Twin technology, and artificial intelligence improves damage detection accuracy and maintenance decision efficiency. Recycling-based rehabilitation methods also contribute to reducing environmental impacts. This study is expected to serve as a reference for developing effective and sustainable road maintenance strategies